Xenon flashlamp driver and control circuit - Tamuri, Abd. Rahman (Penerbit UTM, 2008)
Laser gain media receive excitation energy from a variety of flashtube or flashlamp devices which initiates the process of light amplification. A flashlamp is capable of producing light from energy stored in a continuously ready supply. This light is generally composed of blackbody radiation which includes light energy having frequencies that coincide with the frequencies of transition between the ground states and the pumping bands of the laser medium.